Phytochemical and Biological Studies on the Different Organs of Tanacetum parthenium L. Cultivated in Egypt - MEM Rateb; AAM El-Gendy; SS El-Hawary; AM El - Shamy (Institue of Medicinal Plants, ACECR, 2008)
Phytochemical investigation of Tanacetum parthenium L. family Asteraceae cultivated in Egypt resulted in isolation and identification of four flavonoids. One surface flavonoid was isolated from the fresh leaves and three other flavonoids were isolated from the flower heads. Four sesquiterpene lactones were isolated from the leaves. Two sterols were isolated from the roots. A comparative study of the essential oil content of the leaves and the flower heads was performed using GC/MS. The results revealed the presence of 42 and 30 components in the leaves and the flower heads oil samples, respectively. The major components of both oil samples were camphor (constituted 37.7% and 48.4%) and chrysanthenyl acetate (constituted 33.8% and 26.3%) in the leaves and the flower heads, respectively. Different extracts of T. parthenium L. showed significant biological activities. Analgesic, anti-inflammatory, antipyretic, antispasmodic and uterine-stimulant activities were studied in addition to the in vitro cytotoxic effect.